Application of luteinizing hormone-releasing hormone–ferrosoferric oxide nanoparticles in targeted imaging of breast tumors. Issue 4 (April 2019) - Nian, Di; Shi, Peng; Sun, Junjie; Ren, Li; Hao, Xiaona; Han, Junwei
Background: Ferrosoferric oxide (Fe3 O4 ) nanoparticles are a commonly used magnetic resonance imaging (MRI) reagent. Luteinizing hormone-releasing hormone (LHRH) is highly expressed on the surfaces of tumors, but its expression is low or absent in the corresponding normal tissues, allowing it to be used for targeted imaging and treatment. Methods: We prepared Fe3 O4 nanoparticles using a chemical co-precipitation method, performed coupling with chitosan to prepare LHRH-Fe3 O4 nanoparticles, and explored the application value of LHRH-Fe3 O4 nanoparticles in targeted imaging and treatment of breast tumors through in vitro and in vivo experiments. Results: The particle size of the LHRH-Fe3 O4 nanoparticles was 10 nm, and they could be taken in by human MCF-7 breast cancer cells. The nanomaterial had low cytotoxicity. In vivo MRI experiments showed that LHRH-Fe3 O4 could effectively concentrate on the tumor under the action of a magnetic field. It also had a good negative enhancement effect that significantly reduced the signal intensity of the T2 field, allowing it to be used as a contrast agent of the T2 field. Conclusion: LHRH-Fe3 O4 nanoparticles serve the purpose of targeting contrast agents to target sites and are expected to be used for targeted imaging and treatment of cancers with high LHRH expression.